1954
DOI: 10.1139/v54-104
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Cellulose Acetate Sulphate in Acetone

Abstract: When cellulose acetate sulphate is dissolved in acetone the hydrolysis of the sulphate ester is rapid compared with that of the acetate ester. In 70% acetone the relative rates are reversed. Hydrolysis of the sulphate ester in acetone is greatly affected by the temperature. At 25°C. or greater the hydrolysis is conlplete after 24 hr. A potentiometric titration method has been developed for the estimation of sulphuric acid in the presence of smaller amounts of acetic acid. INTRODUCTIONT h e nitration of cellulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1958
1958
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
(6 reference statements)
1
3
0
Order By: Relevance
“…To con®rm this, experimentation showed that when the samples were dissolved in pure acetone and examined at intervals of 5, 10, 15, 30 min the amount of sulfuric acid was found to increase with the time; and, alternatively, when the samples were dissolved in acetone ± water solutions of lower acetone concentrations, the amount of free sulfuric acid was greatly decreased, and on dissolving in 90 % (vav) acetone ± water solutions no free sulfuric acid was detected in the samples. These results clearly indicate that the use of higher concentrations of acetone (99.0 ± 99.5 % mam) could effect the hydrolysis of the acid sulfate ester and the liberation of free sulfuric acid which was detected by the lead nitrate ± dithizone titration method, and this is in accordance with similar observations noted by Keirstead et al on the hydrolysis of the acid sulfate in high concentrations of acetone (22) .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…To con®rm this, experimentation showed that when the samples were dissolved in pure acetone and examined at intervals of 5, 10, 15, 30 min the amount of sulfuric acid was found to increase with the time; and, alternatively, when the samples were dissolved in acetone ± water solutions of lower acetone concentrations, the amount of free sulfuric acid was greatly decreased, and on dissolving in 90 % (vav) acetone ± water solutions no free sulfuric acid was detected in the samples. These results clearly indicate that the use of higher concentrations of acetone (99.0 ± 99.5 % mam) could effect the hydrolysis of the acid sulfate ester and the liberation of free sulfuric acid which was detected by the lead nitrate ± dithizone titration method, and this is in accordance with similar observations noted by Keirstead et al on the hydrolysis of the acid sulfate in high concentrations of acetone (22) .…”
Section: Resultssupporting
confidence: 92%
“…To minimize the hydrolysis of the acid sulfate ester, Keirstead et al (22) suggested the use of 70 % (vav) acetone ± water concentration. Such concentration, however, was proved unfavourable for the lead nitrate ± dithizone titration method, since, if the water concentration increases above 25 % (vav), the end point will fade titration.…”
Section: Resultsmentioning
confidence: 99%
“…I t has been show11 that the rate of hydrolysis of the sulphate ester of cellulose acetate sulphate depends on various factors of which the liquid medium is coilsidered the most important (1). When cellulose acetate sulphate is dissolved in acetone the hydrolysis of the sulphate ester is rapid compared with that of the acetate ester.…”
Section: Introductionmentioning
confidence: 99%
“…In 70y0 acetone the relative rates are reversed. A t 25" C. or greater, the hydrolysis of the sulphate ester is complete after 24 hours (1). The solvolysis of both the sulphate ester and the acetate ester in acetic acid is well known (2).…”
Section: Introductionmentioning
confidence: 99%